2021
DOI: 10.21037/hbsn.2020.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy versus radiofrequency ablation in patients with small hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Background: This study aimed to compare the clinical outcomes and toxicity between small hepatocellular carcinoma (HCC) patients treated with stereotactic body radiation therapy (SBRT) and those treated with radiofrequency ablation (RFA).Methods: We searched databases for relevant clinical studies. The primary outcomes of interest were overall survival (OS) at 1 and 2 years, freedom from local progression (FFLP) rate at 2 years, and complications.Results: Five cohorts from 5 retrospective studies and 4814 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“… 58 , 59 , 62 The Chinese guidelines, in contrast, recommend radiotherapy for stages IIIa and IIIb. 60 Although evidence seems to be growing that external radiation therapy can benefit patients with HCC, 99 , 100 data are lacking on NAFLD-related HCC. A retrospective study found no difference in overall survival or radiation injury between 87 patients with NAFLD-related HCC or 62 with HBV-related HCC after yttrium-90 radioembolization.…”
Section: Tace and Radiotherapymentioning
confidence: 99%
“… 58 , 59 , 62 The Chinese guidelines, in contrast, recommend radiotherapy for stages IIIa and IIIb. 60 Although evidence seems to be growing that external radiation therapy can benefit patients with HCC, 99 , 100 data are lacking on NAFLD-related HCC. A retrospective study found no difference in overall survival or radiation injury between 87 patients with NAFLD-related HCC or 62 with HBV-related HCC after yttrium-90 radioembolization.…”
Section: Tace and Radiotherapymentioning
confidence: 99%
“…A recent meta-analysis by Hong et al included these previous studies and provided overall treatment outcomes of SBRT compared with RFA ( 3 ). After analyzing five retrospective studies (1 registry-based and 4 single-institution), the authors concluded that SBRT yielded superior local control but inferior overall survival (OS) outcome compared with RFA.…”
mentioning
confidence: 99%
“…We are grateful to Hepatobiliary Surg Nutr for publishing the study entitled “ Stereotactic body radiation therapy versus radiofrequency ablation in patients with small hepatocellular carcinoma : a systematic review and meta - analysis ”. In this well-designed study, the authors concluded that in patients with small hepatocellular carcinoma, stereotactic body radiation therapy has a higher local control rate but poorer prognosis than radiofrequency ablation; in addition, the local toxicity of the two treatments was comparable ( 1 ). While we read the article with pleasure, it must be noted that this study raises some thought-provoking issues.…”
mentioning
confidence: 99%